INFORMATION ABOUT GEORGIAN KINGDOM IN THE WORK AN-NASAVI - Timohin, Dmitrij Mihajlovic (History, Archeology and Ethnography of the Caucasus, 2019)
The Khwarazmian conquest and domination within the South Caucasus had a major impact on the political history of the region, which reduced the influence of the Georgian Kingdom – the strongest political entity in these lands. Experts claim that military and political activity of Jalal ad-Din Manguberdi in this region is the main reason why he joined the Mongol Empire in 1230s’ without resisting the Mongol conquerors. One of the most valuable sources, describing the Khwarazmian invasion to the East Caucasus and the history of Jalal ad-Din Manguberdi’s empire in 1225-1231, is the work of an-Nasawi “Sirat as-sultan Jalal ad-Din Manguberdi”. This historical source is important for understanding the features of political development of the Georgian Empire as the main political opponent of the Khwarazmian kingdom. However, there has been no special study of an-Nasawi’s work as a source on the history of the Georgian kingdom nor in domestic neither in foreign oriental studies. This paper intends to analyze not only the amount of information, provided by an-Nasawi on the Kingdom of Georgia in the course of his description of the Khwarazmian conquest in the South Caucasus, but also some features of said description, and author’s characteristics. Special attention is paid to those lacunas in the description of the South Caucasus, which can be observed in an-Nasawi’s work compared to other historical sources (in the Arabic-Persian, Georgian and Armenian languages). It is equally important to understand the extent to which the author pays attention to the detailed description of the political and military opponent of Jalal ad-Din Manguberdi’s empire, which is the Kingdom of Georgia. It is also important to find out how an-Nasawi pictured and how he reflected in his work the war between Khwarazmian kingdom and the Georgian Empire: as a conflict over territories and spheres of influence or as a religious, even inter-ethnic one.
Keywords: an-Nasavi; Arab-Persian sources; Georgia; Jalal al-Din Mankburny; South Caucasus.